2007
DOI: 10.1002/j.2055-2335.2007.tb00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Trigger Tools for Detecting Adverse Drug Reactions

Abstract: Background Despite the high morbidity and mortality associated with adverse drug events (ADEs) and adverse drug reactions (ADRs) the ability to detect and report them systematically remains inefficient. Aim To investigate if the use of a modified ADE trigger tool could improve the identification of ADRs in hospitals. Method Retrospective review of patients' discharge summaries was conducted at a tertiary care facility over a 5‐week period. A modified ADE trigger tool (based on a previous model) was used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Most (26) of the articles, except two, 27,28 described how the participants were selected. Six of the articles in the study did not state participant inclusion/exclusion criteria explicitly.…”
Section: Quality Assessment Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Most (26) of the articles, except two, 27,28 described how the participants were selected. Six of the articles in the study did not state participant inclusion/exclusion criteria explicitly.…”
Section: Quality Assessment Of Studiesmentioning
confidence: 99%
“…Six of the articles in the study did not state participant inclusion/exclusion criteria explicitly. [27][28][29][30][31][32] Of the 28 studies included, 13 identified and assessed avoidable events separately. 25,26,[31][32][33][34][35][36][37][38][39][40][41] Three studies restricted the analysis to ADRs, clearly excluding the avoidable events.…”
Section: Quality Assessment Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations